Heterogeneous Fenton- and photo-Fenton-like catalytic degradation of emerging pollutants using Fe2O3/TiO2/pillared clays synthesized from aluminum industrial wastes. (April 2023) - Cardona, Yaneth; Węgrzyn, Agnieszka; Miśkowiec, Paweł; Korili, Sophia A.; Gil, Antonio
Abstract: The presence of emerging pollutants (EPs) in water is a major environmental concern. This study evaluates for the first time the removal of three EPs, namely triclosan (TCS), 2, 6-dichlorophenol (2, 6-DCP), and bisphenol A (BPA), 90 μmol/dm 3, from water through both Fenton- and photo-Fenton-like reactions using montmorillonite (Mt) and aluminum interlayered pillared clays (Al-PILC) as catalytic supports. The catalysts (Fe2 O3 /TiO2 /Mt and Fe2 O3 /TiO2 /Al-PILC) were evaluated in single-component solutions and in an equimolar mixture. Two Al-PILC were synthesized from a hazardous waste, namely aluminum saline slag, using either the acid (Al-PILCAE ) or the alkaline (Al-PILCBE ) aluminum extract as precursors. The third Al-PILC was obtained by the conventional method using a commercial aluminum salt (Al-PILCCM ). Catalytic supports were impregnated at 10 and 20 wt% titanium. Iron loadings from 1 to 20 wt% were tested for Mt, while only 20 wt% iron was tested for Al-PILC. All catalysts were characterized using several techniques and the results confirmed the formation of TiO2 and Fe2 O3 . Almost 100 % of TCS and 2, 6-DCP were removed by both Fenton-like (240 and 420 min, respectively) and photo-Fenton-like reactions (30 and 90–120 min, respectively) using the Al-PILC based catalyst. The maximum removal for BPA was 80.14 ± 1.93 % after 120 min under photo-Fenton-like conditions using Al-PILCBE . The catalysts synthesized using the four catalytic supports showed good results for the removal of TCS by both processes, while for 2, 6-DCP and BPA the best results were obtained using Al-PILCAE and Al-PILCBE as catalytic supports. Finally, a degradation pathway was suggested for every pollutant based on the by-products identified during the reactions by HPLC-MS. The results revealed that the materials used in this work are suitable catalysts for removing emerging pollutants from water by both Fenton- and photo-Fenton-like reactions. Graphical abstract: Unlabelled Image Highlights: Aluminum saline slags as aluminum source in the synthesis of Al-PILC Removal of bisphenol A, 2, 6-dichlorophenol and triclosan using Fe2 O3 /TiO2 /Al-PILC Fenton- and photo-Fenton-like degradation of emerging pollutants using Fe2 O3 /TiO2 /Al-PILC